Activity-centered ubiquitous computing support to localized activities - Pinto, Helder (2006)
This paper presents ActivitySpot, a ubiquitous computing framework for supporting localized activities, i.e., activities strongly associated to a specific physical environment, performed by occasional visitors. The ActivitySpot framework implements an activity-centered approach to ubiquitous computing, by defining a conceptual model inspired by Activity Theory and implementing a software infrastructure derived from this conceptual model. ActivitySpot has been evaluated by experiments run at different public spaces and results demonstrate the framework’s suitability to the targeted type of environment.